"Seek the meek, seek the just": Social media and social justice. Issue 9 (October 2015) - Schejter, Amit M.; Tirosh, Noam
Abstract: The latest development of media technology brought about the proliferation of a new media form more often than not dubbed as "social media, " however the catchy "social media" descriptor has not been helpful in surfacing the challenges this new media form raises for governance. In this study we try to tackle that difficulty by addressing the impact on policy of both the four characteristics that we have previously established as making contemporary media stand out from the mass media that preceded them – abundance (of content), mobility, interactivity, and multi-mediality – and their capability to enrich information and make its transference more effective. To do so, we propose to adopt the framework of "social justice" to their governance by describing the philosophy of utilitarianism and its effect on media policy in the twentieth century and preferring the competing twentieth century philosophies of John Rawls and Amartya Sen as the theoretical bases for a new governance framework of social media.